Vaious Methods for Solving Time Fractional KdV-Zakharov-Kuznetsov Equation - Guner, Ozkan; Aksoy, Esin; Bekir, Ahmet; Cevikel, Adem C. (AMER INST PHYSICS, 2016)
This paper presents the exact analytical solution of the (3+1)-dimensional time fractional KdV-Zakharov-Kuznetsov (KdV-ZK) equation with the help of the Kudryashov method, the exp-function method and the functional variable method. The fractional derivatives are described in Jumaries sense.
Keywords: The Kudryashov method; the exp-function method; the functional variable method; the modified Riemann-Liouville dervative; Mathematics; Physics